Oman's Transformation after 1970 - Peterson, J.E., (Middle East and Islamic Studies E-Books Online, Collection 2024., 2024)
Oman's 1970 coup launched a new political and economic structure that was created by and for Sultan Qaboos. The initially haphazard construction matured into a durable structure that continues under Sultan Haitham. This work details the early construction of the Qabusid state in the 1970s-1980s, emphasizing the interplay between personalities and the process of institutionalization. The narrative continues to the present demonstrating the resilience of the Qaboosid system.